2022
DOI: 10.1186/s12955-022-01930-0
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of life of caregivers of breast cancer patients: a cross-sectional evaluation

Abstract: Background The aim of this study was to evaluate the care-related quality of life in caregivers of breast cancer patients, to assess its association with breast cancer patients’ health-related quality of life (HRQoL), and to identify its potential predictors. Methods Caregivers of breast cancer patients at six and twelve months follow up were identified through the institutes electronic patient reported outcome measurement collection tool. The Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Caregiving-related stress can deplete spousal caregivers' emotional and psychological reserves. 51 , 52 ​In addition, participants in this study with less than an elementary school education, rural residence, low income, and ignorance of the HPV had lower QoL, and previous study also found that the QoL of caregivers was significantly correlated with monthly household income. 53 …”
Section: Discussionsupporting
confidence: 54%
“…Caregiving-related stress can deplete spousal caregivers' emotional and psychological reserves. 51 , 52 ​In addition, participants in this study with less than an elementary school education, rural residence, low income, and ignorance of the HPV had lower QoL, and previous study also found that the QoL of caregivers was significantly correlated with monthly household income. 53 …”
Section: Discussionsupporting
confidence: 54%
“…The Cronbach's α coefficient of this scale is 0.861. 14 Social Support Re-Evaluated Scale This scale was created by Xu, with a Cronbach's α coefficient of 0.825-0.896. 15 The scale comprises the following 10 items in three dimensions: objective support (3 items), subjective support (4 items) and degree of utilisation of social support (3 items), with a total score of 12 to 64 points.…”
Section: Activity Of Daily Livingmentioning
confidence: 99%
“…[4,5] Among the chronic diseases of childhood, cancer is more prominent due to its high prevalence rate and its impact on the life of the child and the family. [1,6,7] Chronic illness in a child affects all aspects of family life and all family members. [8][9][10] In the past decade, teams serving children with cancer have attempted to treat childhood cancer diagnosis and treatment as a post-traumatic event for parents.…”
Section: Introductionmentioning
confidence: 99%